Moscow Rules? 'Red' Unionism and 'Class Against Class' in Britain, Canada, and the United States, 1928-1935 - Manley, John (Labour / Le Travail, 2005)
The article analyzes the claims of traditionalist and revisionist historians concerning communism by comparing industrial work of the national socialist parties in Great Britain, the U.S. and Canada in the period 1928-1935. The efforts made by the national parties to strive for leadership of the working class in the workplace are explored. Traditionalist historians are of the opinion that adequate comprehension of communism requires recognition of subordination of each national party to the demands of Moscow, Russia. According to revisionist historians, the national parties enjoyed autonomy in resisting or adapting to the demands of Moscow.
Keywords: Canada; Communism; Comparative studies; GREAT Britain; Labor Unions; SOCIALIST parties; United States; Working class

"Audacity, audacity, still more audacity": Tim Buck, the Party, and the People, 1932-1939 - Manley, John (Labour / Le Travail, 2002)
In 1932, when Communist Party of Canada (CPC) general secretary Tim Buck, six other CPC leaders and one unfortunate rank-and-filer began lengthy sentences in Kingston penitentiary, the Party seemed to have reached its nadir. In fact, martyrdom proved to be a springboard for sustained political revival and was a particular boon to Buck, helping him consolidate a stirring performance in the dock at the Party trial a few months earlier. Until then, he had been considered something of a mediocrity, his status dependent almost entirely upon Moscow's grace and favour. During his three years in Kingston prison, the underground Party successfully reinvented him as the "dauntless leader of the Canadian working class": shortly after his release in November 1934, his five month-long coast-to-coast tour attracted (by the RCMP's almost certainly conservative estimate) a total audience of over 100,000. Buck proceeded to dominate the Party for the remainder of the decade — the Popular Front years — a period fondly recalled in his posthumous memoirs. Buck presented the Popular Front strategy as his — as much as "Moscow's" — invention and quietly attributed the Party's rise in fortunes (membership almost tripled) in large part to his bold and independent political leadership. The Popular Front was certainly good news for Buck, but whether it was good news for "Tim Buck's Party" is more open to question. This paper questions Buck's self-evaluation and suggests that the exposure of the cynical character of the Popular Front project in 1939 "may have planted the seeds of [the] Party's long postwar decline."

The Tailor of Ulm: Communism in the Twentieth Century - Manley, John (Labour / Le Travail, 2013)
The article reviews the book, "The Tailor of Ulm: Communism in the Twentieth Century," by Lucio Magri.
Keywords: 20th century; Communism; History; MAGRI, Lucio, 1932-2011; Nonfiction; TAILOR of Ulm: Communism in the 20th Century, The (Book)

Does the International Labour Movement Need Salvaging? Communism, Labourism, and the Canadian Trade Unions, 1921-1928 - Manley, John (Labour / Le Travail, 1998)
Until the Communist Party of Canada (CPC) turned to the tactic of Class Against Class in 1928-29, it confined its trade-union work almost wholly to "boring from within" the international craft unions of the American Federation of Labor/Trades and Labour Congress of Canada. Although "the party" played a dominant part in the very limited industrial conflict of the 1920s, its attempt to transform the international unions into organs of class struggle was wholly unsuccessful, in part because its "line" presumed a far higher degree of rank and file combativeness than actually existed, and in part because Canadian "labourists" actively resisted its best efforts. Where the CPC believed that the international unions needed to be "renovated," the internationals themselves disagreed. Socialist Plumbers' official John W. Bruce posed the question "Does the International Labour Movement need Salvaging?" which he then answered - to general labourist approval - by reaffirming the progressive character of craft unionism and its tried and tested, non-revolutionary methods. The party's failure to break through this complacency - and labourists' growing resentment of its attempts to do so - predisposed it to accept the Comintern's "New Line" in 1928.

Preaching the Red Stuff: J.B. McLachlan, Communism, and the Cape Breton Miners, 1922-1935 - Manley, John (Labour / Le Travail, 1992)
During the early 1920s the Communist Party of Canada (CPC) established a significant presence in industrial Cape Breton, based on support from the militant minority of the district's unusually combative coal mining union, UMWA District 26, and its charismatic Secretary-Treasurer James Bryson McLachlan. The latter's early recruitment was centrally important in forging what would become enduring political links with rank-and-file militants; it was largely thanks to McLachlan that, through all the ebb and flow of social context and human agency, the party survived the vicissitudes of deteriorating structural conditions and its own tactical blunders (most notably during the ‘third period’), to emerge in the mid-130s with genuinely optimistic prospects. The Scot did not always lead his forces well: like many revolutionary contemporaries his bolshevik temperament was ill-suited to defensive struggle. He nevertheless perceived, and to a limited extent acted upon, the need to construct a defensive communist counter-culture within the struggle for workers' power in the community and the workplace. The embodiment of bolshevik intransigence, McLachlan offered a fixed rallying-point for ‘class fighters,’ especially those who shared his internationalist perspective. Having drawn a new layer of younger militants towards him in 1934-35—and having seen off the CCF in the process—McLachlan could claim to have placed the CPC in its strongest position for a decade.
Keywords: Coal mines & mining; Communism; Communist Party of Canada; History; McLachlan, J.B. (James Bryson); United Mine Workers of America

Communists and Auto Workers: The Struggle for Industrial Unionism in the Canadian Automobile Industry, 1925-36 - Manley, John (Labour / Le Travail, 1986)
During the 1920s and early 1930s the struggle for industrial unionism in the Canadian auto industry was predominantly organized and led by Communist Party members. They, however, had little success with workers whose enjoyment of unusually high industrial wages was tempered by the knowledge that they themselves were almost as replaceable and interchangeable as the parts they assembled. An upswing of industrial militancy in the 1928-9 boom suggested that "Fordism" was not immutable, but any possibility of establishing a "red" auto union disappeared with the arrival of the Depression. Nevertheless, during the grimmest crisis years, Communists kept the idea of industrial unionism alive, and in semi-clandestine conditions built a network of union activists. The formation of the CIO and UAW gave this group the opportunity to turn their aspirations into reality.
Keywords: ACTIVISTS; AUTOMOBILE industry; Canada; Communist Party of Canada; FINANCIAL crises; FORDISM; LABOUR/LE Travail (Book); Labor Unions; PERSONNEL management; Wages

Communism and the Canadian Working Class During the Great Depression: The Workers' Unity League, 1930-1936 - Manley, John (Dalhousie University, 1984)
The Communist Party of Canada's (CPC) attempts to operate the United Front tactics laid down by Lenin and the Comintern in 1920-22 foundered on the CPC's failure to come to terms with the profound character of labour's post-war defeat or with its own marginality. The task of creating a mass party capable of leading, in the not-too-distant future, a revolutionary struggle for power encouraged the CPC to ignore the laborious and modest process of building support around small workplace issues and to prefer working through a spurious united front organization, the Trade Union Educational League, which was little more than a mouthpiece for a succession of abstract propaganda campaigns. When none of these propelled the party to mass status, but rather drove a wedge between it and the Trades and Labour Congress, the ground was prepared for acceptance of the diametrically opposite tactics of the "Third Period", which with much justice have been criticised for their political stupidity. The tardiness with which the CPC applied them underlined the fact that, however much the leaders of the labour movement might have "betrayed" the rank and file, it was hard to see them as "social fascists" who had to be combatted with even more vigour than that usually reserved for the bosses. From the beginning, when they terminated an interesting alliance between the CPC and national unionism, to the end, when they retarded the CPC's recognition of the possibilities opened up by the emergence of the CIO, these tactics had negative consequences. Yet they also helped bring limited political gains for the CPC, which entered the latter half of the 1930s stronger than it had ever been, and organizational advances for the Canadian working class, in the shape of at least the first few bricks in the foundations of mass industrial unionism. In addition, the complementary unemployed movement mobilized tens of thousands of workers and their families against the asperities of the depression. By 1936, the CPC had undeniably "carved out" for itself, a decent niche in the labour movement.
Keywords: Education

The Fate of Labour Socialism: The Co-operative Commonwealth Federation and the Dream of a Working-Class Future - Manley, John (Labour / Le Travail, 2017)
The article reviews the book, "The Fate of Labour Socialism: The Co-operative Commonwealth Federation and the Dream of a Working-Class Future," by James Naylor.

Canadian Communists, Revolutionary Unionism, and the “Third Period”: The Workers’ Unity League, 1929-1935 - Manley, John (Journal of the Canadian Historical Association, 1994)
In compliance with the Third Period "line" of the Communist International (Comintern), the Communist Party of Canada (CPC) launched The Workers' Unity League (WUL) as a centre of "revolutionary" or "red" unionism in December 1929. Until it was "liquidated" during the winter of 1935-6, the WUL had a significance in Canada's Depression labour struggles far outweighing its maximum membership of between 30,000 and 40,000; a significance, moreover, that has yet to be fully acknowledged or analysed. This article seeks to look beyond the conventional view that presents the CPC as a Comintern cipher and the WUL (when it is considered at all) as a "sectarian", "adventurist", "ultra-left" organisation with no real interest in building stable labour unions. While there is no doubt that the two most crucial decisions concerning the WUL — to create it and to liquidate it — were taken in Moscow, neither the Comintern nor the CPC leadership in Toronto was in a position to supervise the implementation of the Third Period line on the ground. Within the broad parameters of the line, local organisers tended to operate as "good trade unionists" rather than "good bolsheviks", using every available opportunity to modify and adapt tactics to local realities. They used their room for manoeuvre to considerable effect, especially during the economic and political upturn of 1933-34, when the WUL led a majority of all strikes and established union bases in a host of hitherto unorganised or weakly organised industries. At the height of its power, however, the WUL knew that it had barely dented the essential mass production industries — auto, steel, rubber, farm machinery. This fact, coupled with the experience of defeat in several key strikes,forced the party to reconsider the WUL's future. Whether the WUL could have survived as part of a national union centre remains open to question. Indisputably, the Comintern terminated that option in 1935.

The Mill: A Worker's Memoir of the 1930s and 1940s - Edwards, Alfred; Manley, John (Labour / Le Travail, 1995)
A literary criticism of the book, "The Mill: A Worker's Memoir of the 1930s and 1940s," by Alfred Edwards. It outlines the characters and the insights provided into the mentality of a section of working class. It examines the author's way of getting the story to its real starting-point in a deft manner. An overview of the story is also given.
Keywords: Criticism; EDWARDS, Alfred; MEMOIRS; MILL: A Worker's Memoir of the 1930s & 1940s, The (Book); Working class

The Sad March to the Right: J. B. McLachlan's Resignation from the Communist Party of Canada, 1936 - Frank, David; Manley, John (Labour / Le Travail, 1992)
The resignation of J.B. McClachlan from the Communist Party of Canada in 1936 is one of the more controversial episodes in the biography of a well-known Canadian labour radical. He was one of the few party leaders to enjoy wide recognition and popular support. His resignation was a difficult personal decision as well as a significant episode in the history of the party. In previous accounts his resignation has been presented ultimately as a repudiation of labour radicalism generally and the Communist Party in particular, as a protest against the adoption of the united front in 1935, or as a form of local and personal political exceptionalism. McLachlan himself made no formal public announcement of his resignation and, except for an impromptu speech at a public meeting in September 1936, he remained largely silent. In response to a letter from party general secretary Tim Buck he prepared a personal explanation of his withdrawal from the party in June 1936. This document, which is reproduced at the end of this article, remains the most important single piece of evidence concerning his resignation. An analysis of the circumstances leading to McLachlan's resignation shows that he did not regard his resignation as a repudiation of basic principles. He had supported the move towards the united front both internationally and domestically but disagreed with the implementation of the policy by the party leadership, especially sa demonstrated in the case of the Amalgamated Mine Workers of Nova Scotia. McLachlan's view of the united front, which he considered to be consistent with the position of the Communist International, stressed the principles of internal democracy and local autonomy in the construction of the united front. In McLachlan's view there were already enough indications to show that leaders such as John L. Lewis had not been fundamentally transformed and that in the long run the decision to endorse an alliance of convenience with the established labour bureaucracy was an ambiguous legacy for the class struggle. In 1936 McLachlan was overtaken by events, but given his own history he was in a position to perceive the difficulties ahead more clearly than most of his contemporaries.
Keywords: ABSTRACTS; BUCK, Tim; Communist Party of Canada; EXCEPTIONALISM (Political science); LABOUR/LE Travail (Book); LEWIS, John L.; MCLACHLAN, James Bryson; MORAL & ethical aspects; Political parties; RESIGNATION from public office